Elevating Cardiac Rehabilitation: A Literature Review of High-Intensity Interval Training's Superior Efficacy in Patients with Heart Failure - Farid Fauzi A M (The International Journal of Medical Science and Health Research, 2025)
INTRODUCTION Heart failure (HF) represents a global epidemic, characterized by profound morbidity, mortality, and escalating healthcare costs (Savarese and Lund, 2022). Exercise-based cardiac rehabilitation (CR) is a Class 1 recommendation for stable HF patients, yet the optimal exercise prescription remains a subject of intense debate (Pelliccia et al., 2024). This systematic review evaluates the efficacy of High-Intensity Interval Training (HIIT) against the traditional standard of care, Moderate-Intensity Continuous Training (MICT), for improving key clinical outcomes in this population. METHODS A comprehensive search of electronic databases (e.g., PubMed, Embase, Cochrane CENTRAL) was performed to identify all randomized controlled trials (RCTs) comparing supervised HIIT to MICT in patients with heart failure (Li et al., 2024). The primary outcome was cardiorespiratory fitness (VO2peak). Secondary outcomes included left ventricular ejection fraction (LVEF), functional capacity (6-Minute Walk Test, 6MWT), and quality of life (Minnesota Living with Heart Failure Questionnaire, MLHFQ) (Li et al., 2024). Data were pooled using a random-effects model. LITERATURE REVIEW The quantitative synthesis of 13 eligible RCTs (n=411) demonstrated a clear and significant advantage for HIIT in patients with heart failure with reduced ejection fraction (HFrEF) (Gomes Neto et al., 2018). Compared to MICT, HIIT was statistically superior for improving the primary outcome of VO2peak (Mean Difference = 1.78 mL/kg/min; 95% CI: 0.80–2.76). Furthermore, HIIT demonstrated statistically significant superiority across all key secondary outcomes: LVEF (MD = 3.13; 95% CI: 1.25–5.02), 6MWT distance (MD = 28.13 meters; 95% CI: 14.56–41.70), and MLHFQ scores (MD = -4.45; 95% CI: -6.25 to -2.64). Critically, subgroup analyses confirm HIIT's superiority remains even in isocaloric protocols, though its benefits appear greatest in long-interval (e.g., 4-minute) protocols. This body of evidence conflicts with findings from large multicenter trials (e.g., SMARTEX-HF), a discrepancy this review analyzes and attributes to critical failures in protocol adherence. CONCLUSION The aggregated evidence confirms that HIIT provides statistically and clinically significant advantages over traditional MICT for improving cardiorespiratory fitness, cardiac function, functional capacity, and quality of life in patients with HFrEF. This effect is protocol-dependent and strongest with long-interval HIIT. The "negative" findings in some large RCTs appear to be artifacts of poor implementation and adherence rather than a failure of the modality itself. These robust findings support the integration of supervised HIIT as a primary training modality within CR programs for HFrEF.